Racial Differences in XO (Xanthine Oxidase) and Mitochondrial DNA Damage-Associated Molecular Patterns in Resistant Hypertension. Issue 4 (15th February 2022) - Butts, Brittany; Brown, Jamelle A.; Denney, Thomas S.; Ballinger, Scott; Lloyd, Steven G.; Oparil, Suzanne; Sanders, Paul; Merriman, Tony R.; Gaffo, Angelo; Singh, Jasvinder; Kelley, Eric E.; Calhoun, David A.; et al.
Abstract : Background: We previously reported increased plasma XO (xanthine oxidase) activity in patients with resistant hypertension. Increased XO can cause mitochondrial DNA damage and promote release of fragments called mitochondrial DNA damage-associated molecular patterns (mtDNA DAMPs). Here, we report racial differences in XO activity and mtDNA DAMPs in Black and White adults with resistant hypertension. Methods: This retrospective study includes 91 resistant hypertension patients (44% Black, 47% female) with blood pressure >140/90 mm Hg on ≥4 medications and 37 normotensive controls (30% Black, 54% female) with plasma XO activity, mtDNA DAMPs, and magnetic resonance imaging of left ventricular morphology and function. Results: Black-resistant hypertension patients were younger (mean age 52±10 versus 59±10 years; P =0.001), with higher XO activity and left ventricular wall thickness, and worse diastolic dysfunction than White resistant hypertension patients. Urinary sodium excretion (mg/24 hour per kg) was positively related to left ventricular end-diastolic volume ( r =0.527, P =0.001) and left ventricular mass ( r =0.394, P =0.02) among Black but not White resistant hypertension patients. Patients with resistant hypertension had increased mtDNA DAMPs versus controls ( P <0.001), with Black mtDNA DAMPS greater than Whites ( P <0.001). Transmission electron microscopy of skeletal muscle biopsies in resistant hypertension patients demonstrates mitochondria cristae lysis, myofibrillar loss, large lipid droplets, and glycogen accumulation. Conclusions: These data warrant a large study to examine the role of XO and mitochondrial mtDNA DAMPs in cardiac remodeling and heart failure in Black adults with resistant hypertension.